DEVELOPMENT OF CREATIVE WRITING ABILITIES BY STORYLINE METHOD WITH JIGSAW TECHNIQUE FOR PRATHOM SUKSA 3 STUDENTS IN PHRA NAKHON SI AYUTTHAYA PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Kongroek, Sumanat; Techawattanasiridamrong, Watcharapat (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aims to 1) Compare academic achievement 2) Study creative writing abilities by using the storyline teaching method combined with the jigsaw technique. Between after studying and the specified criteria of 70 percent 3) Study student satisfaction Using an experimental research format of One-Group Pretest-posttest Design, the tools used in the research were 1) an academic achievement test, 2) a skills training test, and 3) a satisfaction assessment test. The sample group used in the research is: The researcher used group random sampling. There were 30 students in Prathom 3 at Wat Bot Anukul Sangkhakit School. Data analysis and statistics used included mean, standard deviation. and t test. The results were found: 1) The results of the study of academic achievement before and after studying using the storyline teaching method combined with the jigsaw technique. Of students in grade 3 under the Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1, it was found that the academic achievement scores after studying higher than before studying Statistically significant at the .05 level. 2) Results of the study of creative writing ability using the storyline teaching method combined with the jigsaw technique. Of students in grade 3, schools under the Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1, between 70% and the specified criteria, it was found that the students had the ability to write creatively using the story teaching method. Line combined with the jigsaw technique It is 22.73 percent, higher than 70 percent, with statistical significance at the .05 level and 3) Results of the study of student satisfaction with the activity organization Learning in the Thai language subject using the storyline teaching method combined with the jigsaw technique found that students were satisfied with the activity organization. Learning in the Thai language subject using the story line teaching method combined with the jigsaw technique. which overall has the average level at the highest level.